Changes in transitions from private renting to homeownership in the context of rapidly rising house prices. Issue 1 (2nd January 2019) - Sissons, Paul; Houston, Donald
Abstract: A period associated with the emergence of the current housing crisis in Britain provides a testbed in which to investigate household tenure choice in the context of rapidly rising house prices. We compile a bespoke data-set combining data from the British Household Panel Survey and sources of local and national housing and mortgage market information covering the period 1994–2008. During this period, we observe three key changes in behaviour associated with the emergence of the housing crisis: (i) increasing acceptance of long-term renting; (ii) the emergence of local house prices as a factor inhibiting entry to homeownership at district level; and (iii) the cessation of moving to a lower cost district as a strategy to enter homeownership. We interpret these findings as some private tenants reducing their aspiration for homeownership, and those seeking entry to homeownership shifting strategy from moving to cheaper districts in favour of staying put and saving.